2023
DOI: 10.1108/mmms-08-2022-0153
|View full text |Cite
|
Sign up to set email alerts
|

Supervised machine learning techniques for optimization of heat transfer rate of Cu-H2O nanofluid flow over a radial porous fin

Jawad Raza,
Mohsin Raza,
Tahir Mustaq
et al.

Abstract: PurposeThe purpose of this paper is to study the thermal behavior of radial porous fin surrounded by water-base copper nanoparticles under the influence of radiation.Design/methodology/approachIn order to optimize the response variable, the authors perform sensitivity analysis with the aid of response surface methodology (RSM). Moreover, this study enlightens the applications of artificial neural networks (ANN) for predicting the temperature gradient. The governing modeled equations are firstly non-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 39 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…After the digital core image is processed by DCT, it is necessary to analyze the rock physical property based on the compressed image data and establish the physical property prediction model. Numerous studies have shown the efficacy of ANN in constructing precise prediction models [ 33 , 34 , 35 , 36 ]. Hence, employing ANN to train DCT-processed image data for developing permeability prediction models is deemed appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…After the digital core image is processed by DCT, it is necessary to analyze the rock physical property based on the compressed image data and establish the physical property prediction model. Numerous studies have shown the efficacy of ANN in constructing precise prediction models [ 33 , 34 , 35 , 36 ]. Hence, employing ANN to train DCT-processed image data for developing permeability prediction models is deemed appropriate.…”
Section: Introductionmentioning
confidence: 99%